The complementarity of strategic orientations: A meta-analytic synthesis and theory extension - Schweiger, Simone A.; Stettler, Tatiana R.; Baldauf, Artur; Zamudio, César (Strategic management journal, 2019)
Research Summary A firm's strategic orientation has long been of interest in management and strategy research. In particular, entrepreneurial, market, and learning orientations have received thorough theoretical and empirical research attention. In this meta‐analysis, we compare the direct and combined performance effects of these orientations, explore their interrelatedness, and provide a theoretical foundation for complementarity between the three. Building on prior empirical findings from 210 samples and using structural equation modeling and seemingly unrelated regression techniques, we extend the knowledge base on strategic orientations. Our results provide evidence for interrelatedness and complementarity among strategic orientations, indicating that superior firm performance emerges from its capability to align entrepreneurial, market, and learning orientations. Managerial Summary Managers might be tempted to divide rather than combine their attention on various aspects of strategy, such as entrepreneurial, market, and learning orientations. Similarly, organizational culture might inhibit or promote collaboration between distinct organizational functions. We synthesize a vast body of research on firm‐level strategy making and reveal that while each strategic orientation is beneficial on its own, together, the three strategic orientations create synergies that surpass the effects of individual strategic orientations. Therefore, to achieve superior performance, firms need to align their strategy making efforts to (a) monitoring changes in customer needs and competitor moves, (b) engaging in creative processes, and (c) assimilating the extensive knowledge gained from these activities.